Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1021/bi011853m
|View full text |Cite
|
Sign up to set email alerts
|

Duplicated Dockerin Subdomains of Clostridium thermocellum Endoglucanase CelD Bind to a Cohesin Domain of the Scaffolding Protein CipA with Distinct Thermodynamic Parameters and a Negative Cooperativity

Abstract: Mutagenized dockerin domains of endoglucanase CelD (type I) and of the cellulosome-integrating protein CipA (type II) were constructed by swapping residues 10 and 11 of the first or the second duplicated segment between the two polypeptides. These residues have been proposed to determine the specificity of cohesin-dockerin interactions. The dockerin domain of CelD still bound to the seventh cohesin domain of CipA (CohCip7), provided that mutagenesis occurred in one segment only. Binding was no longer detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
75
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 41 publications
6
75
2
Order By: Relevance
“…Although a previous study showed that the Coh-Doc interaction, between 25 and 50°C, was both enthalpically and entropically favorable, there was a linear relationship between the increase in temperature and a decrease in both enthalpy and entropy. Extrapolation of the data of Schaeffer et al (24) to 65°C would also have generated negative entropic and enthalpic values and a K a of 2.5 ϫ 10 7 , Ϸ40ϫ greater than for the Xyn-10B dockerin-cohesin 2 interaction. Recent data by other groups have also indicated that the affinity of different Type I Coh-Doc interactions can vary between pairs.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Although a previous study showed that the Coh-Doc interaction, between 25 and 50°C, was both enthalpically and entropically favorable, there was a linear relationship between the increase in temperature and a decrease in both enthalpy and entropy. Extrapolation of the data of Schaeffer et al (24) to 65°C would also have generated negative entropic and enthalpic values and a K a of 2.5 ϫ 10 7 , Ϸ40ϫ greater than for the Xyn-10B dockerin-cohesin 2 interaction. Recent data by other groups have also indicated that the affinity of different Type I Coh-Doc interactions can vary between pairs.…”
Section: Resultsmentioning
confidence: 96%
“…Recent site-directed mutagenesis studies on the seventh cohesin domain of C. thermocellum CipA (24,27) propose that residues Asp-39, Tyr-74, and Glu-86 and Gly-89 of this domain play a key role in the formation of Coh-Doc complexes and cohesin-cohesin dimers (27). The crystal structure of the CohDoc complex reveals that the equivalent residues in cohesin 2, Asp-39A, Tyr-74A, and Glu-86A, respectively, do indeed interact with the dockerin.…”
Section: Resultsmentioning
confidence: 99%
“…The equivalent residues in the WT dockerin; Asn-44B, Thr-49B, Ser-52B and Arg-23B (N 2), respectively, do not make direct interactions with the cohesin (SI Table 5). Mutagenesis studies support the importance of the polar interactions between the cohesin residues Ala-36A, Asn-37A, Asp-39A, Tyr-74A, Glu-86A, Gly-89A and Glu-131A (26,27) and type I dockerins, although the functional significance of Arg-77A, which seems to make important hydrogen bonds with Arg-23B and Arg-57B at the C-terminal end of the two dockerin binding sites, has not previously been explored.…”
Section: Resultsmentioning
confidence: 99%
“…27 and 30) indicates that both binding sites display similar affinity for the cohesin partner. It is interesting to note that the apparently more polar nature of ligand binding via helix 1 is entropically driven, whereas the more hydrophobic dockerin helix-3 cohesin interaction is associated with a gain in enthalpy (27). Whereas it is currently unclear why the thermodynamic forces driving ligand binding are not reflected in the nature of the amino acids that mediate cohesin-dockerin recognition, the thermodynamic parameters are likely to be influenced by changes in solvation, which cannot easily be explained by static crystal structures.…”
Section: Relative Affinity Of the Two Binding Sites Of The Dockerin Fmentioning
confidence: 99%
See 1 more Smart Citation